2003
DOI: 10.1046/j.1439-0264.2003.00431.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐Related Changes in Rat Optic Nerve: Morphological Studies

Abstract: Age-related changes of the optic nerve were studied in 3-month-old (young), 12-month-old (adult) and 24-month-old (aged) male Sprague-Dawley rats. Cross sections of the intracranial portion of the optic nerves of animals of different age groups were stained with haematoxylin-eosin and examined under a light microscope at low and high magnification. Other sections were stained with crystal violet for demonstration of glial cells. A third group of sections were stained immunohistochemically to detect glial fibri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 17 publications
4
22
0
4
Order By: Relevance
“…Microscopic studies demonstrated that the decrease of nerve fibers and myelin degeneration occurred in the optic nerve of monkey [7,8], human [9], and rat [10] at old age. The authors [26] previously investigated age-related changes of elements in the human cranial and spinal nerves including the optic nerve, using the subjects ranging in age from 65 to 91 years and reported that there were no significant changes of the seven elements in the optic nerve with aging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microscopic studies demonstrated that the decrease of nerve fibers and myelin degeneration occurred in the optic nerve of monkey [7,8], human [9], and rat [10] at old age. The authors [26] previously investigated age-related changes of elements in the human cranial and spinal nerves including the optic nerve, using the subjects ranging in age from 65 to 91 years and reported that there were no significant changes of the seven elements in the optic nerve with aging.…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports on age-related changes of the optic nerve [7][8][9][10], lateral geniculate body [11][12][13][14][15][16], and superior colliculus [17,18], which belong to the visual system. Microscopy and MR imaging revealed that the compositional changes occurred in all of the optic chiasma, lateral geniculate body, and superior colliculus with aging [7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optic nerve, a purely myelinated CNS WM tract (Foster et al, 1982), is one of three models that have been extensively used to study ischemic injury (Agrawal and Fehlings, 1996;Tekkök and Goldberg, 2001). The optic nerve is sensitive to the aging process (Cavallotti et al, 2002(Cavallotti et al, , 2003 and offers several advantages in studying the mechanisms of WM injury including the capacity to quantitatively assess ischemic injury using electrophysiological and immunohistochemical methods.…”
Section: Introductionmentioning
confidence: 99%
“…The optic nerve offers the capacity to quantitatively study the structure-function relationship of WM injury mechanisms. In addition, optic nerve is intrinsically sensitive to the process of aging [16,[25][26][27][28][29], and shows progressive molecular and functional changes as a function of age [16,28,29]. HDAC inhibitors preserve function in both young and aging axons [28,29].…”
Section: Hdac Inhibition Reduces Ischemic Injurymentioning
confidence: 99%